Minefields in their hearts : the mental health of children in war and communal violence - Apfel, Roberta J., 1938-; Simon, Bennett, 1933- (Yale University Press, 1996)
The Holocaust, civil war in Bosnia, drug wars in the cities, random violence in schools, streets, and homes - such events and their aftermath pose special problems for mental health professionals, educators, and others who must help children make sense of acts that endanger them physically and psychically. In this book, edited by Drs. Roberta J. Apfel and Bennett Simon, mental health professionals share their knowledge, experiences, and hopefulness in working with children exposed to war and violence. The result is a moving history of young lives affected by war, persecution, and communal violence, and an invaluable resource for anyone working with children subjected to such traumas.